Evaluation of polypyrrole-polyethylenimine (PPY-PEI) conducting polymers as adsorbents for the removal of methyl orange and crystal violet from polluted solutions / Norhabibah Mohamad - Norhabibah , Mohamad (2023)

(untitled)
Various conducting polymers have emerged as a new adsorbent for the removal of dyes from an aqueous environment. This research study focused on suitable polymeric adsorbents to remove dyes from aqueous solution at a very low cost, ease of preparation, and higher removal efficiency. Novel conducting polymer-based adsorbents, polypyrrole (PPy) and polypyrrole-polyethylenimine (PPy-PEI) have successfully been prepared as new adsorbents and utilized in the adsorption of dyes such as methyl orange (MO) and crystal violet (CV) dyes from aqueous environment. The adsorption characteristics of the prepared polymer-based adsorbents were characterized by the Brunauer-Emmet-Teller (BET) surface analyzer in order to measure the surface area measurements, Fourier transform infrared (FTIR) to identify the functional groups of the prepared adsorbents, X-ray diffraction pattern (XRD) to investigate the crystalline structure and field emission scanning electron microscopy (FESEM) to study the surface morphology of the adsorbents. The highest BET surface area of the PPy-PEI composite (1:1) was found to be 11.85 m2/g, which is much greater than that of the pristine PPy (1:1) of 8.54 m2/g. The performance of PPy-based adsorbents towards the adsorption of MO and CV dyes were investigated by the batch method. PPy-based adsorbents were prepared via chemical oxidative polymerization in the presence of FeCl3.6H2O, anhydrous FeCl3, and (NH4)2S2O8 as oxidants, respectively. Different adsorption parameters such as contact time, adsorbent dose, initial dye concentration and solution pH on the adsorption efficiency of dye removal were explored. The maximum adsorption efficiency of both MO and CV dyes were exhibited using 1:1 mole ratio of monomer to oxidant. The findings confirmed higher dye removal potential in the presence of anhydrous FeCl3 and ammonium persulfate as the oxidant for the MO and CV dye, respectively. The PPy-PEI composite adsorbent has exhibited high adsorption efficiency compared to the pristine PPy adsorbent for the removal of MO and CV dye from aqueous solution. The present work reveals that the incorporation of PEI with Py monomer as a new conducting polymer composite improved the adsorption efficiency of the anionic MO and the cationic CV dyes in aqueous solution. Removal performance was obtained to be 79.1 % and 98.8 % for 100 ppm MO dye by pristine PPy and PPy-PEI composite adsorbents, respectively, at the optimum conditions; pH 3, adsorbent dosage of 0.1 g and with a contact time of 120 minutes. On the other hand, the removal performance for 100 ppm CV dye by pristine PPy and PPy-PEI composite adsorbents was to be 45.0 % and 70.9 %, respectively, at optimum conditions; pH 11, adsorbent dosage of 0.3 g and contact time of 180 minutes. It was observed that the PPy-based adsorbents presented high adsorption performance toward MO than CV dye. Adsorption kinetics was best described by the pseudo-second-order rate model for both dyes. The isotherm study manifested that the Langmuir model was best fitted to the equilibrium data of MO and CV dyes with the maximum monolayer sorption capacity of 232.56 and 142.86 mg/g, respectively at 27 ℃. A regeneration study showed that PPy-PEI could be reused efficaciously for up to three consecutive adsorption-desorption cycles. The combined benefits of facile synthesis and good adsorption potential towards cationic and anionic dyes along with ease of preparation make PPy-PEI a novel adsorbent.